Understanding the Origin of the Hysteresis of High-Performance Solution Processed Polycrystalline SnO2 Thin-Film Transistors and Applications to Circuits - Avis, Christophe; Jang, Jin (Membranes (Basel), 2022)
Crystalline tin oxide has been investigated for industrial applications since the 1970s. Recently, the amorphous phase of tin oxide has been used in thin film transistors (TFTs) and has demonstrated high performance. For large area electronics, TFTs are well suited, but they are subject to various instabilities due to operating conditions, such as positive or negative bias stress PBS (NBS). Another instability is hysteresis, which can be detrimental in operating circuits. Understanding its origin can help fabricating more reliable TFTs. Here, we report an investigation on the origin of the hysteresis of solution-processed polycrystalline SnO2 TFTs. We examined the effect of the carrier concentration in the SnO2 channel region on the hysteresis by varying the curing temperature of the thin film from 200 to 350 °C. Stressing the TFTs characterized further the origin of the hysteresis, and holes trapped in the dielectric are understood to be the main source of the hysteresis. With TFTs showing the smallest hysteresis, we could fabricate inverters and ring oscillators.